2016
DOI: 10.1016/j.clnu.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-D deficiency impairs CD4+T-cell count recovery rate in HIV-positive adults on highly active antiretroviral therapy: A longitudinal study

Abstract: Summary Background & aims We implemented a prospective study among human immunodeficiency virus (HIV)-positive adults to examine the association between vitamin-D deficiency (VDD) and insufficiency (VDI) vs sufficiency (VDS) and CD4+T-cell improvement over 18 months of highly active antiretroviral therapy (HAART). Methods We used data from a randomized placebo-controlled micronutrient trial with 25-hydroxy vitamin-D (25(OH)D) measured at enrollment in 398 adults. CD4+T-cell count was measured repeatedly at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…Although we did not detect a statistically significant interaction between vitamin D levels and HIV status, our findings raise the possibility that the effect of low vitamin D on TB risk may be more pronounced among HIV-positive patients. Studies have shown that among HIV-infected individuals, VDD is associated with deleterious immune activation, 44 lower CD4 counts, 44,45 higher viral loads, 44 and accelerated HIV disease progression. 44,46 Thus, VDD may exacerbate existing immune dysregulation in HIV infection to further increase TB risk or low vitamin D levels may reflect severity of HIV-related immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not detect a statistically significant interaction between vitamin D levels and HIV status, our findings raise the possibility that the effect of low vitamin D on TB risk may be more pronounced among HIV-positive patients. Studies have shown that among HIV-infected individuals, VDD is associated with deleterious immune activation, 44 lower CD4 counts, 44,45 higher viral loads, 44 and accelerated HIV disease progression. 44,46 Thus, VDD may exacerbate existing immune dysregulation in HIV infection to further increase TB risk or low vitamin D levels may reflect severity of HIV-related immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D (VitD) is a key regulator of host defense against infections by activating genes and pathways that enhance innate and adaptive immunity . Several studies have demonstrated that baseline VitD deficiency in HIV‐1‐infected individuals was associated with diminished CD4 + T‐cell recovery after ART initiation . This effect may be partially explained by the fact that sufficient VitD levels can reduce inflammation and T cell activation, restrain HIV‐1 infection in T cells, and promote the proliferation of CD4 + T cells induced by APCs .…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
“…203 Several studies have demonstrated that baseline VitD deficiency in HIV-1-infected individuals was associated with diminished CD4 + T-cell recovery after ART initiation. [204][205][206][207] This effect may be partially explained by the fact that sufficient VitD levels can reduce inflammation and T cell activation, restrain HIV-1 infection in T cells, and promote the proliferation of CD4 + T cells induced by APCs. 207,208 These observations suggest that the baseline metabolic characteristics may be associated with impaired immune reconstitution in HIV-1-infected individuals during ART.…”
Section: Host Metabolic Factorsmentioning
confidence: 99%
“…They also have a higher risk of a respiratory tract infection before this age . VD deficiency is common in HIV‐infected patients, and this appears to be related to faster progression of AIDS, elevated mortality, and a higher risk of mother‐to‐child transmission . Taken together, these results suggest that VD may not only support the innate immune system but also support the adaptive immune system and it plays a role in the fight against pathogens, suggesting the need to guarantee an adequate status, in particular for patients with acute or chronic infections with profound VD deficiency.…”
Section: Role Of Vd In Infectionsmentioning
confidence: 91%